(untitled) (Kronika Bydgoska, 2021)
In the years before the outbreak of the January Uprising, Lublin had witnessed many open demonstrations of national feelings. People organized patriotic manifestations to show their solidarity with the population of the entire Kingdom of Poland. School youth were the most active participants of these activities. Despite the imposition of martial law in October 1861 and the curfew, Lublin middle schoolers posted leaflets at night, calling for change of Russian to Polish signboards, disclosing names of spies and informers. They manifested, against the ban, the signs of national mourning and distributed prohibited publications. The tests of patriotic maturity of the Lublin middle schoolers were the events related to the national uprising in 1863. Graduates and students of the Lublin school participated in gatherings of freedom fighters and took part in battles and actions in the Kingdom of Poland. From among a hundred of alumni of the mentioned school there were many outstanding commanders and officers of guerilla groups. There are not many people in Bydgoszcz and in Kujawsko-Pomorskie Voivodeship who know such names as Maurycy Salutryński, Aleksander Józefowicz, Julian Wieniawski (Jordan), Antoni Skotnicki and Gustaw Wasilewski, whose fight for independence was reported during the period of national uprisings in the area of Wielkopolska.